PENGARUH KOMPETENSI, KERJA TIM DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN TAPANULI TENGAH - Dinar Agnes Eviyanti Gultom; Devi Syahfitri Hasibuan; Benni Irwan Daulay; Marina Novianty T; astuti astuti (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The formulation of problem in this research is there is influence competency on employees performance. There is influence team work on employees performance. There is job culture on employees performance. There is influence of competency, team work and job culture on employees performance. The purpose of this research is for know influence and analize of competency on employees performance. For know influence and analize team work on employees performance. For know influence and analize job culture on employees performance. For know influence and analize competency, team work and job culture on employees performance. The sample in this research is 48 employees, with data analysis technique used is multiple linear regression analysis. The research result competency influence positive and significant on employees performance. Team work influence positive and significant to employees performance. job culture influence positive and significant to employees performance. Competency, job culture and job culture influence positive and significant to employees performance